2009
DOI: 10.1007/s00404-009-0956-9
|View full text |Cite
|
Sign up to set email alerts
|

Intimate partner violence and correlates in pregnant HIV positive Nigerians

Abstract: IPV is common among HIV positive pregnant Nigerians; with a threefold increased risk in women in HIV serodiscordant relationship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
54
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(71 citation statements)
references
References 17 publications
12
54
2
Order By: Relevance
“…This contrasts earlier findings from studies in subSaharan Africa and the United States in which reported IPV was associated with communication of HIV diagnosis (Emusu et al, 2009;Ezechi et al, 2009;Gielen et al, 1997;Gielen et al, 2000;Maman et al, IPV AND HIV IN UGANDA 2001;Medley, Garcia-Moreno, McGill, & Maman, 2004;WHO, 2003;Zierler et al, 2000). Probably, this may be due to the fact that previous studies in which IPV was associated with communication of HIV diagnosis were conducted in specialized urban antenatal clinics, STD clinics, or urban voluntary counselling and HIV testing (VCT) centers.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…This contrasts earlier findings from studies in subSaharan Africa and the United States in which reported IPV was associated with communication of HIV diagnosis (Emusu et al, 2009;Ezechi et al, 2009;Gielen et al, 1997;Gielen et al, 2000;Maman et al, IPV AND HIV IN UGANDA 2001;Medley, Garcia-Moreno, McGill, & Maman, 2004;WHO, 2003;Zierler et al, 2000). Probably, this may be due to the fact that previous studies in which IPV was associated with communication of HIV diagnosis were conducted in specialized urban antenatal clinics, STD clinics, or urban voluntary counselling and HIV testing (VCT) centers.…”
Section: Discussioncontrasting
confidence: 72%
“…Intimate partner violence (IPV) is physical, sexual, or psychological/emotional abuse that occurs between two people in a close relationship (Centers for Disease Control and Prevention [CDC], 2011;Ezechi et al, 2009) and includes current and former partners including boyfriend or girlfriend relationships (Coker et al, 2002;Ezechi et al, 2009;Saltzman, Fanslow, McMahon, & Shelley, 2002). IPV is a phenomenon of epidemic proportions prevalent in many communities and cultures.…”
Section: Introductionmentioning
confidence: 98%
“…We found that 16% of women in Nigeria had experienced IPV within the past 12 months, which falls within the range of global estimates of 15% to 50% (Garcia-Moreno et al). Studies in developing countries have shown that women experiencing IPV are more likely to be infected with HIV and STIs (Adebayo et al, 2010;Ezechi et al, 2009) and men who physically abused their female partners are also more likely to engage in higher-risk sex and to be infected with HIV and STIs (Dunkle et al, 2004;Silverman et al, 2007Silverman et al, , 2008. Given a society where both extramarital sex and IPV are largely perceived as normal (Antai & Antai, 2008;Ezechi et al, 2004;GarciaMoreno et al;Orubuloye, Caldwell, & Caldwell, 1993;Orubuloye et al, 1997aOrubuloye et al, , 1997bSmith, 2007), programs to change community and individual attitudes toward these two critical issues are important, especially in relation to men's recognition of their civic responsibilities to their partners' health and well-being.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, evidence from South Africa and Asia demonstrates that there is an increased risk for HIV infection among women experiencing intimate partner violence (IPV) (Dunkle et al, 2004;Kalichman et al, 2005Kalichman et al, , 2007 Modie-Moroka, 2009); and IPV has been linked to greater HIV and STI infection (Adebayo, Fahrmeir, Seiler, & Heumann, 2010;Ezechi et al, 2009;Silverman, Decker, Kapur, Gupta, & Raj, 2007;Silverman, Decker, Saggurti, Balaiah, & Raj, 2008). However, no study has examined the association between IPV and extramarital sex (or sexual concurrencies) in Nigeria.…”
Section: Introductionmentioning
confidence: 94%
“…[28,30] The relationship between IPV and HIV is also bidirectional. Some women are at increased risk of IPV following disclosure of their HIV-positive status [27,[31][32][33][34][35] or following screening during pregnancy. [31,35,36] With the implementation of Option B+ in antenatal services, where antiretroviral treatment is initiated on HIV-positive status confirmation in pregnant women, adherence rates decline after delivery, particularly in women who have not disclosed their HIV status to their partner, thereby enhancing their risk of progressing to AIDS and dying.…”
Section: Guest Editorialmentioning
confidence: 99%